Personal hygiene as a risk factors of helminthiasis among primary school students in Asia and Africa: a literature review - Rohmah, Fitri Anisai; Setiawan, Rachman; Adriyani, Retno; Mohd Sham, Shaharuddin (Universitas Airlangga, 2022)
Introduction: Helminthiasis becomes one of the infectious diseases included in neglected diseases that receive less attention and mostly occurred in tropical countries. The World Health Organization (WHO) in 2020 stated that helminthiasis spread throughout sub-Saharan Africa, America, China, and East Asia where 60% suffered by children. STH infections may result from poor hygiene in many school aged-children, especially in primary school. This article was written to analyze the personal hygiene of primary school children that may affect the incidence of helminthiasis. Discussion: An integrative literature review was conducted using databases, from Google Scholar, Pubmed, Research Gate, and Science Direct databases. It was 24 articles consisting of 20 articles published by international journals and 4 articles in Indonesian journals. Most of the infectious agents in Asia were Ascaris lumbricoides and Trichuris trichiura, while Ascaris lumbricoides, Hookworms, and Trichuris trichiura dominate in Africa. Poor personal hygiene may a risk of infection. For example, children in Asia do not cut their nails or wash their hands. While children in Africa do not wash their hands, walked barefoot, and conducted open defecation. Conclusion: Personal hygiene of primary school children has a positive effect on the incidence of helminthiasis in Asia and Africa with different prevalences. To prevent and control helminthiasis in school children, schools should provide education about personal hygiene, improve sanitary facilities, and routinely give anthelmintics every six months.